Revisiting the Death Railway, The Survivors’ Accounts, by Sasidaran Sellapah - Viswanathan Selvaratnam (Kajian Malaysia, 2021)
Sasidaran Sellappah, although not trained as a professional historian, must be commended for his enthusiasm and commitment to research and publication of this study entitled Revisiting the Death Railway: The Survivors’ Account. The book restores to life a virtually forgotten, grim and horrendous saga of human suffering that a huge number of lower-class Malayans were subjected to eight decades ago. The main thrust of the book is to highlight the brutal human anguish and deaths endured under the hands of the ruthless and sadistic Imperial Japanese Army, both by the Asian workers, nearly half of whom were Malayans, as well as the Australian, British, Dutch and American prisoners of war (PoWs), who suffered daily during the construction of Japan’s strategic Burma-Siam Railway notoriously known as the “Death Railway”.